Assessment of Literacy Training Activities by the Literacy and Development Through Partnership in the Tolon District - Mohammed, D. H. (University of Ghana, 2014)
Little attention has been paid to literacy assessment in developing countries including Ghana. The objective of the research work was to conduct an assessment of literacy training activities by the Literacy and Development through Partnership (LADP) including assessment of the performance of learners in numeracy, reading and writing, the application of literacy skills in the lives of adult learners and the facilitation method used by the LADP. The study was basically a case that employed quantitative research design. It sampled four literacy classes or communities out six literacy classes at the writing stage where numeracy and reading has already been taught and writing underway. Convenient sampling was used to select the four literacy classes but learners were selected using simple random sampling with the lottery method. Data was collected using test questions, focus group discussion and interviews and analyzed using means and standard deviations, and themes and patterns. The assessment of literacy training activities of the Literacy and Development through Partnership showed that learners performed well in both in reading and numeracy but performed below average in writing. In the Gbulahagu community learners performed better in numeracy with a mean of 23.40 and Standard deviation (SD) value of (7.356), followed by reading mean of (21.87) and SD (5.489) and then writing mean (17.73) and SD (4.464). In the Dimabu community learners performed better in numeracy with a mean of (28.07) and an SD of (1.486), followed by reading mean (28.07) and SD of (3.416) and then writing mean of (17.40) and an SD of (5.489). In the Kunkulung community learners performed better in reading with a mean of (22.00) and an SD of (7.00), followed by writing with a mean of 15.33 and an SD of 4.923 then numeracy with a mean of (15.27) and an SD of (4.877). In the Nysherigu community learners performed better in reading with a mean of (26.27), and an SD of (2.086) followed by numeracy with a mean of (19.93) and then writing mean (12.27) and an SD of (3.494). In terms of cross case comparisms in literacy skills performance, the following were discovered. In terms of numeracy performance, the Dimabu community performed better with a mean of (28.07) and SD of (1.486), followed by Gbulahagu with a mean of (23.40) and an SD of (7.356), Nysherigu, a mean of (19.93) and an SD of (4.667) and Kunkulung, a mean of (15.27) and an SD of (4.667). In terms of reading performance, the Nysherigu community performed better than all the other communities with a mean of (26.27), and an SD of (2.086) followed by Dimabu with a mean of (25.33) and an SD of (3.416), Kunkulung, a mean of (22.00) and an SD of (7.00) and Gbulahagu, a mean of (21.87) and an SD of (5.489). In terms of writing performance, the Gbulahagu community performed better with a mean of (17.73) and an SD of (4.464), followed by Dimabu, a mean of (17.40) and an SD of (5.489), Kunkulung, a mean of (15.33) and an SD of 4.923 and Nysherigu, a mean of (12.27) and an SD of (3.494) in that order. In terms of overall performance in literacy skills assessment, learners performed better in reading skills with a mean of (95.84) and an SD of (17.991), followed by numeracy skills with a mean value of (85.97) and an SD of (18.386) then writing skills assessment with a mean of (62.73) and a standard deviation of (18.37). The assessment also showed that learners regardless of the social context of the literacy program could transfer the skills of literacy in their personal and daily lives. The method of facilitation used by facilitators in the literacy program is the Gudshinsky method of facilitation which facilitators had difficulties teaching the writing component of the method. This could be partly the cause of their weak performance in writing. It is recommended that more emphasis should be put in teaching learners writing skills and provide in more materials that will enable learners practice writing in order to improve on program delivery and performance.
Thesis (MPhil) - University of Ghana, 2014
Keywords: Literacy Training; Development Partners; Developing Countries; Ghana